APLIKASI E-MONITORING PENGADAAN STUDI KASUS ULP KABUPATEN PURWAKARTA - Nur Alamsyah; Lutfi Amar (Jurnal Elektra, 2019)
Procurement of goods/services should meet principles of procurement as regulated in Presidential Regulation Number 4 of 2015 on the Fourth Amandement of Presidential Regulation Number 54 of 2010 on Governmental Procurement of Goods/Services. Generally, a procurement process needs a longer time, higher cost, as well as a higher number of persons involved. It is a challenge for a government, especially ULP Kabupaten for example a direct procurement. Thus, monitoring on a direct procurement is required. An application has developed with aim to monitor the procurement process, started from procurement planning until receipt process of goods/services. The model used for the application development is waterfall model. According to the testing conducted in ULP Kabupaten Purwakarta, the application was succeeded to record whole steps of procurement including receipt step, to assist the admin of procurement officer to find out each progress of procurement in real time, and to provide reporting data.